Fermat Curve Path Planning Method for Ship Trajectory Tracking - Li, Daoke (Informatica, 2024)
13003886586@163.com Abstract: Traditional ship motion systems are no longer sufficient to meet the navigation demands of vessels. Therefore, a path planning method based on Fermat curves is proposed in this study. Within the ship operation system, Fermat curves are employed to enhance straight-line paths, achieving smooth motion between waypoints. The Fermat curve path planning method is integrated into ship guidance algorithms to guide vessel headings. The performance of the proposed guidance algorithm is evaluated, and experimental results indicate that the algorithm can maintain a high similarity between actual and desired trajectories. In comparison to traditional Line-of-sight methods, the proposed algorithm demonstrates shorter path planning lengths. Additionally, the algorithm's heading angles can compensate for sideslip angles in perturbed environments. Comparative experiments with other guidance algorithms reveal that the proposed algorithm has the shortest runtime, saving more energy. Furthermore, it achieves accuracy and precision rates of 87.1% and 91.3%, respectively, surpassing other algorithms and providing high-precision guidance for vessels. In terms of error comparison, the proposed algorithm keeps guidance errors around 2, showcasing superior performance and feasibility in ship path guidance.